Assessing the value of state legislative experience and legislative professionalism in national election performance, 1974–2010. Issue 3 (1st September 2017) - Waggoner, Philip D.
Abstract: State legislative experience and chamber professionalism have been shown to benefit state legislators as they decide and prepare to run for national office in American Congressional elections. Yet, what are the effects of these two factors on national election performance? I test the implications from the literature that state legislative experience and chamber professionalism should impact national election outcomes on all two-party contested elections from 1974 to 2010. I find that state legislative experience enhances candidates' vote shares, though differently for different candidates. Yet, surprisingly professionalism plays no moderating role. Such effects present at the earlier stages of elections wash out as elections come to a close.